1980
DOI: 10.1111/j.1365-2044.1980.tb05043.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and cardiac arrest

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In vitro and animal studies have not shown a difference in calcium ionization between the two intravenous preparations (103). In addition, there have not been data to support a difference during cardiac arrest (104). Either preparation can be administered, with knowledge that different amounts of calcium are present in the same volume.…”
Section: Management Of Calcium Abnormalitiesmentioning
confidence: 93%
“…In vitro and animal studies have not shown a difference in calcium ionization between the two intravenous preparations (103). In addition, there have not been data to support a difference during cardiac arrest (104). Either preparation can be administered, with knowledge that different amounts of calcium are present in the same volume.…”
Section: Management Of Calcium Abnormalitiesmentioning
confidence: 93%